2017
DOI: 10.1016/j.gpb.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leaf Transcriptome in Banksia Hookeriana

Abstract: Banksia is a significant element in vegetation of southwestern Australia, a biodiversity hotspot with global significance. In particular, Banksia hookeriana represents a species with significant economic and ecological importance in the region. For better conservation and management, we reported an overview of transcriptome of B. hookeriana using RNA-seq and de novo assembly. We have generated a total of 202.7 million reads (18.91 billion of nucleotides) from four leaf samples in four plants of B. hookeriana, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…There are few genomic resources for either macadamia or within the Proteaceae. Transcriptomic data are available for Macadamia ( Chabika et al 2020 ) and other Proteaceae genera including Banksia ( Lim et al 2017 ), Grevillea ( Damerval et al 2019 ) , Protea ( Akman et al 2016 ) and Gevuina ( Ostria-Gallardo et al 2016 ) , and have been utilized to help to understand the evolution of floral architecture ( Damerval et al 2019 ) and variation in locally adaptive traits ( Akman et al 2016 ). Recent genome wide association studies in macadamia have identified markers associated with commercially important traits ( O’Connor et al 2020 ) but their location and context in the genome is unknown.…”
mentioning
confidence: 99%
“…There are few genomic resources for either macadamia or within the Proteaceae. Transcriptomic data are available for Macadamia ( Chabika et al 2020 ) and other Proteaceae genera including Banksia ( Lim et al 2017 ), Grevillea ( Damerval et al 2019 ) , Protea ( Akman et al 2016 ) and Gevuina ( Ostria-Gallardo et al 2016 ) , and have been utilized to help to understand the evolution of floral architecture ( Damerval et al 2019 ) and variation in locally adaptive traits ( Akman et al 2016 ). Recent genome wide association studies in macadamia have identified markers associated with commercially important traits ( O’Connor et al 2020 ) but their location and context in the genome is unknown.…”
mentioning
confidence: 99%
“…Transcriptomic data from Proteaceae species are scarce and have mostly been obtained from leaves for specific purposes: in Leucadendron to derive phylogenetic markers (Tonnabel et al, 2014), in Protea repens to study population differentiation in relation to local adaptation (Akman et al, 2016), in Banksia hookeriana to derive SSR markers (Lim et al, 2017) and in Gevuina avellana to study heteroblastic development under different light conditions (Ostria-Gallardo et al, 2016). In Macadamia integrifolia , a reference transcriptome was built from flowers, shoots and leaves, in parallel to a draft genome (Nock et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Raw reads produced from the sequencing were scrutinized for quality in terms of total raw reads, total clean reads, Q20 percentage (proportion of nucleotides (NTs) with quality value > 20), N percentage (proportion of unknown NTs in clean reads), and GC percentage. Sequence reads with adaptors of unknown NTs (numbering > 5%) or low quality (reads with quality values ≤ 10), representing more than 20%, were discarded by filter_fq software, and only high-quality sequence reads were retained for assembly [52]. The Trinity software package was used to assemble the data into unigene collections from each of the 12 cDNA libraries [53].…”
Section: Methodsmentioning
confidence: 99%